Impact of Temperature and Relative Humidity on PMD in Directly Buried Optical Fibre Cables in Semi-Arid and Tropical Highlands in Kenya - Moses Ndunda; Alix Dehayem-Kamadjeu; David Waswa (International Journal of Optics)
The telecommunication industry has implemented fibre deployment guidelines that reliably safeguard cable health during installation in the field. While installed fibre cables remain buried in the field, temperature and moisture in the locality subject them to mechanical expansions and corrosion. Directly buried fibre cables experience accelerated degradation that results from exposure to harsh environments. This increases pulse spreading and overlaps, with a mean time duration, known as Differential Group Delay (DGD), on the signal, as it propagates along the cable. DGD is stochastic; thus, Mean DGD is determined and presented as Polarization Mode Dispersion (PMD). This work undertook a real life assessment of how fluctuations in temperature and relative humidity influence PMD in directly buried fibre optical links, in a case study that focused on the fibre cable network owned by Liquid Telecom Kenya. The network spans across two key climatic ecosystems, namely, rift valley highlands and northern lowlands. The analysis revealed that fibre cables experience higher PMD in semi-arid areas by a factor of 2.6, compared to highland areas.